Letramentos e ressignificação da prática docente por meio da ferramenta digital EDMODO - Gaudêncio, Wanda Patrícia de Sousa (2015)
This study aims to present the results of an intervention in a classroom in order to reframe the teaching practice with the acquisition of digital literacy through the use by students of Edmodo digital tool. Characterized as a qualitative study, with descriptive and interventional character, was developed with students of the 7th year in a public school located in the neighborhood of Catingueira (Acacio Figueiredo) in Campina Grande-PB. To reach our goals, research is structured in the following stages: analysis and exploitation of Edmodo tool, setting the students to the platform interface, application didactic sequence and analysis of activities for investigation to favor practices of literacies among participating students. Data collection and the results achieved with the intervention led us to the introduction of new practices and that the incentive for writing a multiliterated perspective is valid, since activities are applied to permit access, analysis, production and socialization texts in different languages and still, that allow the student access to new conceptions of reading and analyzing texts. As a theoretical basis, we based on authors who talk about computer science, the relation between technology and education, literacy, multi literacy, digital literacy and assessing the feasibility of Edmodo social interaction platform, like Xavier et al (2011); Almeida et al (2000), Alves, Zambalde and Figueiredo (2004); Almeida and Fonseca Junior (2000); Sousa, Moita and Carvalho (2011); Coscarelli and Ribeiro (2011); Moreira and Caleffe (2008); Gabriel (2013); Bisognin (2009); Marcuschi (2008), and Shephered Salies (2013), Trjara (2008), Tanzi Neto (2013), Valente (1997). As the methodological procedures, an intervention through the application of a didactic sequence with cellular support the use was conducted for carrying out activities in the platform Edmodo.